(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2019)
Microorganisms from thirty soil samples from various locations in West Sumatera was screened for their ability to grow on xenobiotics such as acrylamide, propionamide, polyethylene glycol (PEG) 1000, Sodium dodecyl Sulfate (SDS), Sodium dodecylbenzene sulfonates (SDBS), diesel and phenol. The screening media contain all of these xenobiotics as carbon sources, ammonium sulphate as nitrogen sources and trace elements. The growth of these microorganisms on the xenobiotics was monitored at A600 nm on a microplate. Of the isolates screened, the number of bacterial isolates than can grow on acrylamide, propionamide, polyethylene glycol (PEG) 1000, SDS, SDBS, diesel and phenol were 23, 22, 13, 17, 3, 17 and 17, respectively, all as carbon sources. These xenobiotics-degrading isolates can be further utilized in the future as bioremediation agent.